Viable but non-cultivable state in oral microbiota: a critical review of an underexplored microbial survival strategy - Mahdizade Ari, Marzie; Scholz, Konstantin Johannes; Cieplik, Fabian; Al-Ahmad, Ali (Frontiers in Cellular and Infection Microbiology, 2025)
The viable but non-cultivable (VBNC) state and persister cells, two dormancy phenomena in bacteria, differ in various aspects. The entry of bacteria into the VBNC state as a survival strategy under stressful conditions has gained increasing attention in recent years, largely due to the higher tolerance of VBNC cells to antibiotics and antimicrobials resulting from their low metabolic activity. The oral cavity favors biofilm growth in dental hard tissues, resulting in tooth decay and periodontitis. Despite advances in VBNC state detection in the food industry and environment, the entry capability of oral bacteria into the VBNC state remains poorly documented. Furthermore, the VBNC state has recently been observed in oral pathogens, including Porphyromonas gingivalis, which shows potential relevance in chronic systemic infections, Enterococcus faecalis, an important taxon in endodontic infections, and Helicobacter pylori, which exhibits transient presence in the oral cavity. Further research could create opportunities to develop novel therapeutic strategies to control oral pathogens. The inability of conventional culture-based methods to identify VBNC bacteria and the metabolic reactivation of dormant cells to restore susceptibility to therapies highlights a notable gap in anti-VBNC state strategies. The lack of targeted approaches tested for efficacy against VBNC bacteria underscores the need to develop novel detection methods. This review discusses the VBNC state, its importance in public health, and diagnostic techniques, with a special focus on the VBNC state in oral bacteria.